2001
DOI: 10.1002/1522-2683(200109)22:16<3514::aid-elps3514>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of protein adsorption patterns onto differently charged hydrophilic superparamagnetic iron oxide particles obtainedin vitro andex vivo

Abstract: Protein adsorption patterns of superparamagnetic iron oxides (SPIO) were evaluated by two-dimensional electrophoresis (2-DE) after in vitro incubation of the particles in plasma or serum. SPIO particles having positive (MKK 1211), negative (MKA 1211), or neutral (MKG 1411) charge were used. Protein adsorption patterns of different charged SPIO particles acquired in vitro and recollected 5 min after intravenous injection into rats (ex vivo) were compared. For the uncharged MKG 1411 particles, the differences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Similarly, free MPIOs injected in the tail vein could also be engulfed by macrophages and transported to the brain, although the possibility exists that their uptake by macrophages might be prevented by the zeta potential of the macrophages as well as the MPIOs. The zeta potential is an indicator of the degree of repulsion between adjacent cells, and it is significant since it has been demonstrated that since both MPIOs (35) and macrophages (36) have a high degree of negative charge, the uptake of MPIOs by macrophages is inhibited in certain situations. The possibility also exists that an initial accumulation of MPIOs at the lesion site might be due to the enhanced permeability and retention (EPR) effect, whereby certain sizes of molecules tend to accumulate in certain tissue types (37, 38), and these MPIOs may have subsequently been taken up by the local activated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, free MPIOs injected in the tail vein could also be engulfed by macrophages and transported to the brain, although the possibility exists that their uptake by macrophages might be prevented by the zeta potential of the macrophages as well as the MPIOs. The zeta potential is an indicator of the degree of repulsion between adjacent cells, and it is significant since it has been demonstrated that since both MPIOs (35) and macrophages (36) have a high degree of negative charge, the uptake of MPIOs by macrophages is inhibited in certain situations. The possibility also exists that an initial accumulation of MPIOs at the lesion site might be due to the enhanced permeability and retention (EPR) effect, whereby certain sizes of molecules tend to accumulate in certain tissue types (37, 38), and these MPIOs may have subsequently been taken up by the local activated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…To answer the question, if there are certain fiber-specific characteristics within the protein-corona of fibers, we compared the "top-ten" or "hit list" of the proteins found on fibers and other nanomaterials of different shapes and materials: i.e., CNTs, silica nanoparticles [87,88], gold nanoparticles [89][90][91], polymeric particles [27,88,92], and iron oxide nanoparticles [93,94]. Despite the differences in morphology (shape and size), surface characteristics and material composition, several proteins (e.g., albumin, apolipoprotein AI and E, fibrinogen, fibronectin, vitronectin, complement factor C3, α2-macroglobulin) were found on nearly all protein coronas investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Muhler reports that LN uptake of carboxydextran-coated, 20 nm (mean) sized USPIOs (Table 1, DDM128N fraction) in LN was similar before and after complement depletion with cobra venom factor and is, therefore, independent of C3 binding. 16 In another report, more than 10 plasma proteins were found to bind to the surface of negative, neutral, or positive SPIOs by 2D-gel electrophoresis, and C3 was not one of these proteins 17 (Table 1, SPIO-Lind). The protein levels differed significantly between the particle variants.…”
Section: Opsonizationmentioning
confidence: 95%
“…In another report, more than 10 plasma proteins were found to bind to the surface of negative, neutral, or positive SPIOs by 2D‐gel electrophoresis, and C3 was not one of these proteins (Table , SPIO‐Lind). The protein levels differed significantly between the particle variants.…”
Section: Relevance Of Sizementioning
confidence: 97%